Determinants of Low Birth Weight Newborns in Indonesia: Literature Review - Rachmawati, Reza; Yuliani, Nur Rohma (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2022)
LBW is a health problem that requires special attention in various countries, especially in developing countries with low socio-economic conditions. LBW has a greater risk of experiencing morbidity and mortality than babies born with normal weight. Factors that affect low birth weight (LBW) are teenage pregnancy, preeclampsia, anemia, and ANC visits. LBW is also one of the factors that can cause babies to die before reaching the age of 1 year. The purpose of this systematic literature review is to analyze the relationship between maternal age, preeclampsia, anemia, and ANC visits to determine the cause of LBW so that it can suppress IMR. Using the Critical Appraisal Skills Program (CASP) method with data sources obtained from PubMed, Google Scholar, and Research Gate, there are 145 articles reviewed. Inclusion criteria were (1) Teenage pregnancy, infant; (2) the incidence of LBW; (3) Factors influencing the incidence of LBW; (4) Full text; (5) Articles published from 2017 to 2021; and (6) national journals. There are 5 articles that meet the inclusion criteria. The results of this literature review are the factors that affect low birth weight (LBW), namely Teen Pregnancy, Preeclampsia, Anemia, and ANC visits.